Effective Management of Subsidiaries in Commercial Banks on The Example of China Merchants Bank - Xiulian Zhang; Denis Paleev (Communications of International Proceedings, 2021)
An important strategic task of the socio-economic development of China is the creation of a competitive banking system, which, on the one hand, determines the financial foundation of the national economy, and on the other hand, serves as an indicator of the effectiveness of banking management. The development of the financial market dictates the revision of the principles of commercial banks' activities, the basis of which is the creation of competitive advantages. In order to increase the competitiveness of commercial banks, a management system is needed that includes the organization and implementation of measures to enhance competitive advantages. The main element of such a system is the assessment of competitiveness, aimed at determining the factors that contribute to an increase in the efficiency of the bank's activities.
Keywords: Effective Management; Subsidiaries; Commercial Bank; Stakeholders.